(untitled) (Global Journal of Medical Research, 2021)
Bone metastases under de knee and elbow (acrometastasis) are rare. We present the case of a patient diagnosed with lung adenocarcinoma, with a lesion in the right proximal radius. Radiological imaging through CT and MR suggested metastatic lesion, which anatomopathological results confirmed. As the presence of these markers provides a poor outlook, radiotherapy was initially considered. However, given the clinical stability of the patient and the limited amelioration observed, surgical treatment was finally conducted.